2020
DOI: 10.1021/acsnano.0c04620
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics-Limited Two-Step Growth of van der Waals Puckered Honeycomb Sb Monolayer

Abstract: Puckered honeycomb Sb monolayer, the structural analog of black phosphorene, has been recently successfully grown by means of molecular beam epitaxy. However, little is known to date about the growth mechanism for such puckered honeycomb monolayer. In this study, by using scanning tunneling microscopy in combination with firstprinciples density functional theory calculations, we unveil that the puckered honeycomb Sb monolayer takes a kinetics-limited two-step growth mode. As the coverage of Sb increases, the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
13
0
2
Order By: Relevance
“…33 Meanwhile, Shi et al showed that the distorted hexagonal-like Sb lattice formed on the SnSe substrate at the initial stage will eventually transform into the energetically favorable α-Sb. 34 As the surface structures and chemical compositions of WTe 2 , MoTe 2 , PdTe 2 , and Bi 2 Se 3 are rather similar, these behaviors suggest that there might be a competition between the αand β-phases when an antimonene sheet is epitaxially grown on a substrate and that the final structure of antimonene might be tuned by the substrate. However, a comprehensive understanding on the controllable growth of αand β-Sb by the choice of substrates is still missing, which should be vital for the preparation and practical applications of antimonene and analogues.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…33 Meanwhile, Shi et al showed that the distorted hexagonal-like Sb lattice formed on the SnSe substrate at the initial stage will eventually transform into the energetically favorable α-Sb. 34 As the surface structures and chemical compositions of WTe 2 , MoTe 2 , PdTe 2 , and Bi 2 Se 3 are rather similar, these behaviors suggest that there might be a competition between the αand β-phases when an antimonene sheet is epitaxially grown on a substrate and that the final structure of antimonene might be tuned by the substrate. However, a comprehensive understanding on the controllable growth of αand β-Sb by the choice of substrates is still missing, which should be vital for the preparation and practical applications of antimonene and analogues.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Hogan and co-workers reported that α-Sb prepared on Bi 2 Se 3 can undergo a phase transition to β-Sb by gentle annealing . Meanwhile, Shi et al showed that the distorted hexagonal-like Sb lattice formed on the SnSe substrate at the initial stage will eventually transform into the energetically favorable α-Sb . As the surface structures and chemical compositions of WTe 2 , MoTe 2 , PdTe 2 , and Bi 2 Se 3 are rather similar, these behaviors suggest that there might be a competition between the α- and β-phases when an antimonene sheet is epitaxially grown on a substrate and that the final structure of antimonene might be tuned by the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to other elemental 2D materials, phase engineering can be realized via delicately tuning the substrate temperature and using appropriate substrates. Black-phosphorus like antimonene can be stabilized on Bi 2 Se 3 after room temperature (RT) deposition, and transforms to blue-phosphorus like phase after annealing at 473 K due to the perfect lattice match . The phase transition of 2D materials from puckered to buckled phase has shown to be a general trend via bond breaking pathway when taking into the substrate into account.…”
Section: Resultsmentioning
confidence: 99%
“…也阻碍了对a-Sb进一步的电学性质的 测量. 2019年, Shi等 [83] 利用分子束外延(molecular [75] . 法、脉冲激光法、液相剥离法、酸辅助剥离法以及 分子束外延法等多种方法合成铋烯 [86−90] .…”
Section: 锑 烯unclassified